Thinking about the patient's wishes: practical wisdom of discharge planning nurses in assisting surrogate decision‐making. Issue 4 (31st January 2017) - Kageyama, Yoko; Asano, Midori
Abstract : Background: The accelerating trend towards shorter hospital stays in Japan has made modes of decision‐making essential for effective patient transition from the hospital to recuperation in the regional community, and the ageing of the population has brought a rise in surrogate decision‐making by the families of patients lacking decision‐making ('self‐decision') capacity. Aim: To verbalise and elucidate the practical wisdom of discharge planning nurses by focusing on the perceptions and judgements, they apply in practice and describing their methodology in concrete terms. Research method: Participants were six discharge planning nurses and one person with previous experience as a discharge planning nurse, all working at discharge planning departments of acute care hospitals. Separate, semi‐structured, interactive interviews were conducted with each participant. The study design was qualitative descriptive in form with qualitative content analysis. All participants provided written informed consent to participate in the study, which was approved by the study institution. Results: Three concepts were extracted as the basis for discharge planning nurses' perception and judgement at acute care hospitals: working for mutual envisionment of the available postdischarge options; helping the family act as spokesperson(s) for the patient's wishes; and understanding the family inclusive of the patient as a relationship of strongly interaffecting interests. Conclusion: The practical wisdom of the nurse, working in mutual envisionment with the family, and collaborative decision‐making through discussion with those who know the patient, leads to rational discharge assistance.